Telaah Kitab al-Mustashfa dan Maslahah Mursalah al-Ghazali - Achmad Lubabul Chadziq (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2024)
This study aims to examine the monumental work Al-Mustashfa by Imam Al-Ghazali in the discipline of ushul fiqh, particularly in the context of the discussion on maslahah mursalah. The primary focus of this research is to understand how Imam Al-Ghazali structured this book by combining rational (philosophical) and textual (scriptural) methods, as it was composed using the methodology of scholars of ilm kalam or the Shafi’i school. The study also concentrates on Al-Ghazali’s perspective on maslahah mursalah.This research employs a descriptive-analytical method. The study finds that Imam Al-Ghazali, in writing Al-Mustashfa, uses the term istislah to refer to maslahah mursalah. He categorizes it among weak arguments (dalil-dalil) leading scholars to differing perceptions about whether Al-Ghazali regarded maslahah mursalah as authoritative evidence (hujjah). However, upon a more comprehensive analysis of his works on ushul fiqh, it can be concluded that he considered it a valid hujjah under the condition that it does not contradict the Qur'an, Hadith, or consensus (ijma), and aligns with the objectives of Islamic law (maqasid shari’ah). These conditions have led scholars to argue that maslahah mursalah, according to Al-Ghazali, is a non-independent proof (dalil ghair mutaqillah), but its application closely resembles qiyas.